ANALYSIS OF WEAPON TECHNOLOGY AND DEFENSE RESOURCES USED IN THE INDONESIAN GUERRILLA WAR 1945 – 1949 - Khoerozadi Faizal Iman; Robertus Heru Triharjanto; Heri Budi Wibowo; Novky Asmoro; Tsaniyah Wulandari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Guerrilla War strategy became an important part of the history of Indonesia's struggle. The limited weapon technology and defense resources used in the Guerrilla War made the choice of strategy become important. Therefore, an analysis of the utilization of weapon technology and defense resources used during Indonesian Guerrilla War from 1949 to 1949 will provide a deeper understanding of how limited resources can be effectively utilized in the struggle for independence. This method uses a qualitative method with a narrative/historical approach to analyze the utilization of defense equipment technology and weaponry resources in the period of the Indonesian guerrilla war in 1945-1949. Through this analysis, it can be seen that the guerrilla strategy succeeded in maximizing the potential and effectiveness of limited weaponry resources. Environmental factors, battle tactics, and the courage of fighters were successful in maintaining independence. In the perspective of asymmetrical warfare, Indonesia's guerrilla warfare strategy succeeded in balancing superior forces.